ACQUISITION AND PRESENTATION OF DIGITAL EVIDENCE IN CRIMINAL TRIAL IN INDONESIA - Giri Santosa, Dewa Gede; Ibnu Kamali, Karell Mawla (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
Digital evidence is not included in the types of evidence as stipulated in Article 184 paragraph (1) of the Criminal Procedure Code, but is regulated in Law No. 11 of 2008 concerning Electronic Information and Transactions as amended by Law No. 19 of 2016. However, it is often found that the submission of digital evidence is not only for criminal cases related to electronic information and transactions, but also for criminal cases that are not regulated in the Law on Electronic Information and Transactions. Furthermore, distinct characteristics of digital evidence compared to evidence in general require different acquisition and presentation method. Hence the writers intends to examine the method of acquisition and presentation of digital evidence in criminal trial and how judges evaluate digital evidence by examining how it was obtained and presented to the trial. This research is normative legal research, where the data sources include research on legal principles, legal system, and legal comparison. From the research, it was concluded that Indonesia already has laws and regulations governing the expansion of evidence to include digital evidence, Indonesia also has rules regarding the method of acquisition and presentation of digital evidence in the criminal trial. Therefore, judges are required to be able to evaluate the validity of digital evidence by observing the method of acquisition and presentation of digital evidence in the criminal trial based on applicable laws.